1976
DOI: 10.1007/bf02756559
|View full text |Cite
|
Sign up to set email alerts
|

A non-standard representation for Brownian Motion and Itô integration

Abstract: A number of authors have attempted to apply Nonstandard Analysis to Probability Theory. Unfortunately, the nonstandard reformulations heretofore proposed have retained most of the essential difficulties inherent in the standard formulations. As a result, the application of nonstandard techniques has met with limited success. Hersh [4] produced a nonstandard analogue of Wiener measure. His "measure", however, is not countably additive; moreover, it is supported on a countable subset of C([0, 1]). Using a differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
88
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 185 publications
(88 citation statements)
references
References 5 publications
0
88
0
Order By: Relevance
“…For example, Ward Henson [9] extended their procedure to represent essentially every finitely additive probability measure. Rohit Parikh and Milton Parnés [19,20] showed that the technique could be used to define the conditional probability P(A\B) for any pair of subsets of [0,1], retaining translation invariance.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Ward Henson [9] extended their procedure to represent essentially every finitely additive probability measure. Rohit Parikh and Milton Parnés [19,20] showed that the technique could be used to define the conditional probability P(A\B) for any pair of subsets of [0,1], retaining translation invariance.…”
mentioning
confidence: 99%
“…Loeb [16] extracted standard harmonic measure on an ideal boundary and maximal representing measures for positive harmonic functions as distributions of internal measures. The author [1] constructed Wiener measure on C([0,1]) as the distribution of an internal measure v on *C([0,1]); this was possible even though there is a countable B G C([0,1]) such that v(*B) = 1. It is highly doubtful that either of these constructions could be carried out usefully without the use of measure-preserving maps.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been clear for some time now that the Loeb-measure of nonstandard analysis [11] may be useful in the construction of different kinds of limit measures. Indeed, Anderson's nonstandard construction of a Brownian motion [1] may be regarded as a direct construction of a weak limit measure (compare Billingsley [4]). Work on weak convergence from a nonstandard point of view has been carried on by Anderson and Rashid [3], and Loeb [12].…”
mentioning
confidence: 99%